The sun also rises - Hemingway, Ernest, 1899-1961 (Vintage classics., 2022)
"Hemingway's famous first novel tracks the Lost Generation of the 1920s from the nightclubs of Paris to the bullfighting arenas of Spain. Ernest Hemingway, winner of the Nobel Prize in Literature in 1954, exerted a lasting influence on fiction in English through his economical prose style that conceals more than it reveals. His first novel, published in 1926, is narrated by world-weary journalist Jake Barnes, who is burdened by a wound acquired in World War I and by his utterly hopeless love for the flamboyantly decadent Lady Brett Ashley. The Sun Also Rises is both a tragic love story and a searing group portrait of hapless American expatriates drinking, dancing, and chasing their illusions in postwar Europe."--